THE STUDY OF LONGITUDE DISPERSION PHENOMENON IN FLOW PROBLEMS THROUGH LAPLACE TRANSFORM TECHNIQUE - Patel, Shailesh S. (IJRDO -JOURNAL OF MATHEMATICS, 2016)
The present paper discusses the phenomenon of longitudinal dispersion in the flow of two misciblefluids through porous media. An exact solution of partial differential equation arising in thisphenomenon has been obtained by Laplace Transform method. A particular case of the formersection by regarding flow velocity and dispersion coefficient as constants, and has been solved bymethod of Laplace transformation. The phenomenon of longitudinal dispersion is the process bywhich miscible fluids in laminar flow mix in the direction of flow has been discussed.